Evaluating the Impact of Alcohol Abstinence on the Cognitive Functioning of Adults Diagnosed with Alcohol Use Disorder - Mostert, Sonja (University of Pretoria, 2021)
Dissertation (MA (Psychology))--University of Pretoria, 2021.